Bibliometric analysis of photodynamic therapy and immune response from 1989–2023 - Fan, Wanting; Tang, Jianming; Tang, Su; Lin, Zhengshen; Li, Mohan; Zhang, Zheng; Wu, Donglei (Frontiers in Pharmacology, 2024)
Objective: Photodynamic therapy (PDT) is a minimally invasive treatment approach for precancerous and cancerous lesions, known for its ability to activate the host immune response. This study conducted a bibliometric analysis to identify the research trends and hotspots related to the immune response in PDT. Methods: We analyzed articles and reviews published from 1989 to 2023, retrieved from the Web of Science database. Using Citespace and VOSviewer, we visualized the distribution patterns of these studies in time and space. Results: The analysis revealed a substantial increase in the number of publications on PDT-related immune response since 1989. A total of 1,688 articles from 1,701 institutions were included in this analysis. Among thei nstitutions, the Chinese Academy of Sciences demonstrated exceptional productivity and a willingness to collaborate with others. Additionally, 8,567 authors contributed to the field, with Mladen Korbelik, Michael R. Hamblin, and Wei R. Chen being the most prolific contributors. The current research focus revolves around novel strategies to enhance antitumor immunity in PDT, including PDT-based dendritic cell vaccines, combination therapies with immune checkpoint inhibitors (ICIs), and the use of nanoparticles for photosensitizer delivery. Furthermore, genes such as CD8A, TNF, CD4, IFNG, CD274, IL6, IL10, CALR, HMGB1, and CTLA4 have been evaluated in the context of PDTrelated immunity. Conclusions: PDT not only achieves tumor ablation but also stimulates the immune response, bolstering antitumor immunity. This study highlights the emerging hotspots in PDT-related immune response research and provides valuable insights for future investigations aimed at further enhancing antitumor immunity.